Perancangan Pengolahan Sampah Modern Dengan Pendekatan Arsitektur Modern Di Tangerang Selatan - Rio Ichsan Pratama; Putri Suryandari; Harfa Iskandaria (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
Garbage is one of the main factors in urban or regional environmental problems that are being faced in this era of globalization in line with the increasing number of residents and population activities. Garbage is a problem in many big cities. Including in the South Tangerang City area. In South Tangerang City itself, it produces 400 tons per day which is accommodated at the Cipeucang TPA. The Cipeucang TPA in the South Tangerang area still uses an open dumping system, but this location is getting full. Cipeucang TPA in the near future will no longer be able to accommodate garbage from South Tangerang City. Modern Waste Management in South Tangerang City was built to meet all needs by recycling waste by minimizing the amount of existing waste consisting of facilities such as Organic/Inorganic Waste Processing, Organic/Inorganic Recycling Production Building, B3 Warehouse, Workshop, Foodcourt, Sewage Water Treatment Plant, and other Supporting Buildings. This Modern Waste Management applies the theme of Modern Architecture, very suitable to be applied to designs located in South Tangerang City, with designs that form follow function, namely the shape of the building adapts to the character of the waste processing itself so that it is in accordance with the functions and considerations of tactical building users. The facade of the building will also use materials that support modern concepts such as the application of ACP material, glass, and exposed concrete to highlight the solid impression of the building. Keywords: Modern Architecture, Modern Waste Management, South Tangerang City.